HM Preferensi Konsumen Terhadap Keputusan Pembelian Buah Lokal Dan Impor Gudang Cek Nia 15 Ulu Palembang: Preferensi Konsumen Terhadap Keputusan Pembelian Buah Lokal Dan Impor Gudang Cek Nia 15 Ulu Palembang - henny malini; Mangatur Rajagukguk; Reshi Wahyuni (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2026)
This study aims to analyze consumer perceptions and preferences and their influence on purchasing decisions of local and imported fruits at Gudang Cek Nia,15 Ulu Palembang. The research employed a survey method with accidental sampling involving 40 respondents. Data were collected through questionnaires and interviews, then analyzed using a Likert scale and binary logistic regression with the assistance of SPSS. The variables analyzed included service, price, and quality. The results showed that consumer perceptions of service at Cek Nia Warehouse were in the good to very good category. Consumer preferences for local fruits were rated as good, while preferences for imported fruits were rated as fairly good. The logistic regression analysis indicated that price, quality, and service significantly influence purchasing decisions of local and imported fruits. This study is expected to provide useful considerations for business actors in improving marketing strategies and service quality.